2005
DOI: 10.1021/ja056611e
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Cluster and Density Functional Theory Studies of the Vibrational Contribution to the Optical Rotation of (S)-Propylene Oxide

Abstract: In a previous study (Chemical Physics Letters 2005, 401 , 385) we computed the optical rotatory dispersion of (S)-propylene oxide in gas phase and solution using the hierarchy of coupled cluster models CCS, CC2, CCSD, and CC3. Even for the highly correlated CC3 model combined with a flexible basis set, the theoretical gas-phase specific rotation at 355 nm was found to be negative in contrast to the experimental result. We argued that vibrational contributions could be crucial for obtaining a complete understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
102
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(104 citation statements)
references
References 40 publications
2
102
0
Order By: Relevance
“…This would tend to place doubts on the analyses of optical activity contributions in EPB, suggesting that the conformer specific [a] k,h parameters are in error or that complete exclusion of vibrational dynamics is an oversimplification. 25,[35][36][37][38][39] The disparate behavior seen for the three epoxide systems targeted by the present study might also reflect the greater degrees of conformational freedom available to the ethyl group of EPB as opposed to the less flexible halomethyl substituents of ECH and EFH.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…This would tend to place doubts on the analyses of optical activity contributions in EPB, suggesting that the conformer specific [a] k,h parameters are in error or that complete exclusion of vibrational dynamics is an oversimplification. 25,[35][36][37][38][39] The disparate behavior seen for the three epoxide systems targeted by the present study might also reflect the greater degrees of conformational freedom available to the ethyl group of EPB as opposed to the less flexible halomethyl substituents of ECH and EFH.…”
Section: Resultsmentioning
confidence: 90%
“…While the restriction of calculations to localized conformer geometries greatly facilitates evaluation of ensemble-averaged properties, this approximation has excluded vibrational degrees of freedom and their potentially important influence upon chiroptical effects. 25,[35][36][37][38][39]61,62 Likewise, our theoretical description of solvation has been limited to an implicit (continuum dielectric) model that neglects the detailed nature of solute-solvent interactions in the cybotactic region. This treatment has enabled solvent-mediated changes in conformer structures and populations to be estimated, but attendant modifications in chiroptical behavior caused by the surrounding medium (as reflected in the dynamical response of the solvent to oscillating electric and magnetic fields) 51 have not been taken into account.…”
mentioning
confidence: 99%
“…The experimentally determined 61 rotation is 4.78 (dm g/cm 3 ) 21 and the correct sign is obtained with CCSD only after addition of the ZPVC, confirming that vibrational corrections are particularly important for small-angle optical rotation. 20,30 It should be noted, however, that more diffuse basis sets as well as higher-order electron correlation effects could improve the description of the excited electronic states which, in turn, could have a significant impact on the computed electronic optical rotations. Overall, the results of the present investigation indicate that it may be more important to employ CCSD for the calculation of the optical rotation at the equilibrium geometry than to include vibrational effects.…”
Section: Resultsmentioning
confidence: 99%
“…22 In the case of methyloxirane, vibrational effects must be taken into account to reproduce the experimental gas phase optical rotation to within a few degrees. [27][28][29][30] For conformationally flexible molecules, a simple Boltzmann procedure has been applied to average the electronic contributions from different conformations. 5,25,[31][32][33][34][35][36][37][38] Comparing to a rigorous vibrational averaging procedure involving all conformations of 3-chloro-1-butene, Crawford and Allen 26 have shown that the simple approach benefits from cancellation of errors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation